Health inequality and the uses of time for workers in Europe: Policy implications - J. Gimenez-Nadal; Jose Molina (IZA Journal of European Labor Studies, 2016)
This paper analyses the relationship between health inequality and the time allocation decisions of workers in six European countries, deriving some important policy implications in the context of income tax systems, regulation of working conditions, and taxes on leisure activities. Using the Multinational Time Use Study, we find that a better perception of own health is associated with more time devoted to market work activities in all six countries and with less time devoted to housework activities for both men and women. However, the evidence for the associations between health and leisure is mixed. This study represents a first step in understanding cross-country differences in the relationship between health status and time devoted to a range of activities for workers, in contrast with other analyses that have mainly focused only on market work. A better understanding of these cross-country differences may help to identify the effects of public policy on inequalities in the uses of time.
Keywords: D13; J16; J22; 330; Health; Time allocation; Inequality; Multinational time use study